2014
DOI: 10.4103/2229-5178.126034
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of oral zinc therapy in epidermodysplasia verruciformis with squamous cell carcinoma

Abstract: Epidermodysplasia verruciformis (EV) is a rare, inherited disorder that predisposes patients to widespread human papillomavirus (HPV) infection and cutaneous squamous cell carcinomas. There is still no definitive therapeutic modality for EV. A 24 year old male patient with EV was treated with oral zinc sulphate, one of the cheapest and safe immuno-modulator available as therapeutic agent with satisfactory result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Zinc was proven to be used as topical or systemic oral therapy in previous studies for treatment of warts [ 29 , 30 ]. Only few studies used it intralesional and showed favorable results as those done by (Mohamed [ 7 ] , Moubasher [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zinc was proven to be used as topical or systemic oral therapy in previous studies for treatment of warts [ 29 , 30 ]. Only few studies used it intralesional and showed favorable results as those done by (Mohamed [ 7 ] , Moubasher [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients should be advised to use sunblock from childhood [ 2 ]. In another case, zinc therapy was used for treating EV, with a response rate of 20% to 40%, without a recurrence after six months [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In an open-label study in Korea, the effectiveness of oral zinc sulfate 10 mg/kg for 2 months in the treatment of patients with nongenital viral warts was assessed and 50% of patients showed a complete resolution ( Mun et al, 2011 ). Sharma et al (2014) reported the clearance of recalcitrant warts in a patient with epidermodysplasia verruciformis in 12 weeks with oral zinc (10 mg/kg/day). In addition, some evidence showed that a combination therapy of oral zinc sulfate with conventional treatments of vulvar warts appeared to reduce the relapse rate of genital warts ( Akhavan et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%